First case of parthenogenesis in ladybirds (Coleoptera: Coccinellidae) suggests new mechanisms for the evolution of asexual reproduction. (17th November 2019) - Magro, Alexandra; Lecompte, Emilie; Hemptinne, Jean‐Louis; Soares, Antonio O.; Dutrillaux, Anne‐Marie; Murienne, Jérôme; Fürsch, Helmut; Dutrillaux, Bernard
Abstract: Parthenogenesis, the development of unfertilized eggs resulting in the exclusive production of female offspring, is rare in animals relative to sexual reproduction and is mainly reported in invertebrates. It has been hypothesized that polyploidy, hybridization and endosymbiont infections are its major causal events but the mechanisms triggering asexual reproduction remain unclear. Here, we study the proximate causes at the origin of parthenogenesis in the first reported case of asexuality in the Coccinellidae (Coleoptera). The asexual populations were found in the Azores and the Mascarene archipelagos, and were identified as Nephus voeltzkowi Weise, a bisexual species widespread in sub‐Saharan Africa. The specimens from both populations are diploid but present different karyotypes and heterozygosities that evoke hybrid origins, commonly associated with parthenogenesis in Coleoptera. However, the close proximity of their genomes (99.8% homology for the complete mitochondrial genome and 99.9% for the complete nuclear ribosomal cluster) together with the congruence between the mtDNA tree and the nuclear tree, and the low heterozygosity levels, suggests that the two populations are not hybrid. We propose that they belong to a single chromosomally polymorphic species undergoing Robertsonian fusions. Furthermore, specimens from both populations are infected with Wolbachia (supergroup B strain), contrary to sympatric bisexual species of the same genus. Although Wolbachia has been shown to induce parthenogenesis in haplodiploid organisms, it has been recently suggested that it could also induce parthenogenesis in hosts with other sex determination systems. Whether chromosome rearrangements and/or Wolbachia infections are post‐parthenogenetic events or are at the origin of parthenogenesis still needs to be determined. Abstract : We report here the existence of all‐female populations, genetically similar and identified as Nephus voeltzkowi Weise, in the Azores and the Mascarene. Laboratory experiments confirmed they reproduce via thelytokous parthenogenesis, and we combined different approaches to investigate the proximate mechanisms at its origin. Our results reject polyploidization and strongly support a non‐hybrid origin. In contrast, we identified chromosome rearrangements and a Wolbachia infection in parthenogenetic individuals. We cannot exclude they are proximal causes of parthenogenesis.